Risk Assessment of Total Coliform in X WTP’s Water Production Using Failure Mode And Effect Analysis Method - Bella Apriliani Amanda; Atiek Moesriati; Nieke Karnaningroem (TEKNIK, 2017)
The greatest risk of drinking water supply is a failure to provide safe drinking water for communities. Based on IPA Kedunguling testing report on March 2016 noted that sample exceeding the quality standart of Peraturan Menteri Kesehatan RI No 492/2010 for the total coliform quality standart. The presence of total coliforms indicating water contamination by pathogen means the water is not safe to consume. The disinfection process has an importance rule in pathogen inactivation. Disinfectant performance is influenced by temperature, pH, turbidity, and the presence of organic materials. One way to control the quality of water produced by using a risk management approach Failure Modes and Effect Analysis (FMEA) methods. The potential risks should be measured to determine causes of the problems and find the appropriate risk reduction. The risk assessment is using Risk Priority Number (RPN) scale as a basis prioritization of remedial action on issues. Based on identification and risk analysis using FMEA known that the greatest risk of failure is the stipulation of chlorine dose and organic substances (category of high risk level); residual chlorine (category of moderate risk level); turbidity and pH (very low risk level category). Improvement proposal that can be done to reduce total coliforms presence in IPA Kedunguling is by increasing residual chlorine to 0.6 mg/l, set a daily chlorine level, controlling DBPs forming by lowering the concentration of organic precursor using granular activated carbon (GAC) or aeration, by lowering the dose of disinfectant, set aside DBPs after the compound is formed using granular activated carbon (GAC), turbidity and pH monitoring, and regularly washing the filters